Obstructive sleep apnea is associated with increased QT corrected interval dispersion: the effects of continuous positive airway pressure - Bilal,Nagihan (2018)
Abstract Introduction: Severe obstructive sleep apnea is associated with increased QT corrected interval dispersion and continuous positive airway pressure is thought to improve this arrhythmogenic marker. Objective: The aim of the study was to determine the decrease of ratio of cardiovascular risk in patients with obstructive sleep apnea. Methods: The study included 65 patients with severe obstructive sleep apnea who had an apnea-hypopnea index score of >30. Each patient underwent 12-channel electrocardiogram monitoring and polysomnography. Patients with an apnea-hypopnea index score of <5 were used as the control group. The control group also underwent electrocardiogram monitoring and polysomnography testing. The QT corrected interval dispersion levels of both groups were calculated. Three months after continuous positive airway pressure treatment, electrocardiogram recordings were obtained from the 65 patients with severe obstructive sleep apnea again, and their QT corrected interval dispersion values were calculated. Results: There were 44 male and 21 female patients with severe obstructive sleep apnea syndrome. The age, gender, body mass index, initial saturation, minimum saturation, average saturation, and desaturation index were determined in both groups. The QT corrected intervals of the obstructive sleep apnea patients (62.48 ± 16.29 ms) were significantly higher (p = 0.001) than those of the control group (29.72 ± 6.30 ms). There were statistically significant differences between the QT corrected values before and after the continuous positive airway pressure treatment, with pretreatment QT corrected intervals of 62.48 ± 16.29 ms and 3-month post-treatment values of 41.42 ± 16.96 ms (p = 0.001). There was a positive and significant correlation between QT corrected interval dispersion periods and the apnea-hypopnea index and hypopnea index in obstructive sleep apnea patients (p = 0.001; r = 0.71; p = 0.001; r = 0.679, respectively). Conclusion: Continuous positive airway pressure treatment reduced the QT corrected interval dispersion in patients with severe obstructive sleep apnea. In addition, shortening the QT corrected interval dispersion periods in patients with severe obstructive sleep apnea may reduce their risk of arrhythmias and cardiovascular disease.